The Influence of Promotion, Product Quality, and Brand Image on Buyer Decisions and the Implications for Customer Satisfaction - Suharno, FA Suharno; Zambri, Mohammad; Edy Wibowo, Sunaryo; Hadi Winoto, Suryadi; Taryono (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
This research aims to analyze promotions, product quality, and brand image on purchasing decisions and their implications for customer satisfaction. The research was structured in the form of Cluster Stratified Random Sampling with a sample size of 325 respondents, the Alanisis Method used Structural Equation Modeling (SEM). The research results concluded that the total influence of the Product Quality variable on customer satisfaction for Small Industrial Village (PIK) products is in the Fair to Good category, this indicates that customer satisfaction is not optimal. The magnitude of the influence of Brand Image on Purchase Decisions for Small Industrial Village Shoe Products (PIK) with a total influence of 21.09 percent. Meanwhile, the magnitude of the influence of Promotion on Purchasing Decisions for Small Industrial Village Shoe Products (PIK) has a total influence of 23.57 percent, while the magnitude of the influence of Purchasing Decisions on Customer Satisfaction from Small Industrial Village Shoe Products (PIK) has a total influence of 80.51 percent.